Hubungan Tingkat Pendidikan, Pengetahuan, dan Dukungan Suami dengan Praktik Pemberian ASI Eksklusif pada Ibu Bekerja di Klinik Pratama Sunggal - Bali , Florentina Aspienti Regnat Killianis; Laia , Firina; Gulo, Indah Mawati; Rangkuti, ⁠Ifrina; Nababan, Tiarnida; Duha, Yantriani (Journal of Pharmaceutical and Sciences, 2025)
Background: The low rate of exclusive breastfeeding in Indonesia (52.5% in 2021), particularly in North Sumatra (57.83%), remains a pressing public health issue, especially among working mothers. Educational level, knowledge, and husband support are strongly suspected to influence the success of exclusive breastfeeding, yet these factors have been underexplored in the context of primary clinics in urban areas such as Sunggal. Objective: To analyze the relationship between educational level, knowledge, and husband support with exclusive breastfeeding practices among working mothers at the Sunggal Primary Clinic.Methods: This quantitative, cross-sectional study involved 30 working mothers selected through total sampling. Data were collected via questionnaires and interviews, then analyzed using Chi-Square tests and logistic regression to measure the strength of associations (OR). Results: Statistical analysis showed significant relationships between all three independent variables and exclusive breastfeeding practices (p<0.05). Husband support emerged as the most dominant factor with an odds ratio (OR) of 8.2 (95% CI: 2.1–32.4), followed by maternal knowledge (OR=5.6; 95% CI: 1.8–17.3) and educational level (OR=4.3; 95% CI: 1.5–12.4). Specifically, mothers who received strong support from their husbands were 8.2 times more likely to successfully provide exclusive breastfeeding compared to those who did not. Likewise, mothers with good knowledge were 5.6 times more likely to succeed, and highly educated mothers were 4.3 times more successful than those with limited knowledge and education. Multivariate analysis indicated interaction among these three factors, with husband support amplifying the positive effects of education and knowledge. Among respondents who possessed all three positive factors (higher education, good knowledge, and strong husband support), 86.7% successfully provided exclusive breastfeeding, while only 13.3% succeeded in the group lacking these factors. Conclusion: This study strengthens the evidence that family-based interventions focusing on enhancing the husband’s role, along with comprehensive education, can be an effective strategy to increase exclusive breastfeeding rates among working mothers. These findings highlight the need for clinic policies that integrate lactation counseling for couples.